Efek broken home terhadap regulasi emosi dan kesejahteraan psikologis remaja - Cahyanti, Elisa Tika (Maliki Interdisciplinary Journal, 2025)
Adolescent psychological development is influenced by various factors, including family roles, social experiences, and modern life challenges. This study aims to analyze several aspects of adolescent psychology such as resilience, empathy, forgiveness, and the role of family education in promoting mental well-being. Through a literature study from recent sources, it is found that parental involvement plays a crucial role in shaping a child’s emotional balance, while empathy and the ability to forgive contribute to adolescents’ social and emotional growth. Furthermore, adolescents who experience cyberbullying exhibit varying levels of resilience depending on their social support systems. This study also highlights the importance of gratitude in maintaining adolescents’ mental health. By understanding these dynamics, more effective psychological interventions can be designed to optimally support adolescent development.